2015
DOI: 10.1107/s1600576715018464
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth of Ru-doped congruent LiNbO3and investigation of crystalline perfection and optical properties

Abstract: Single crystals of undoped and Ru-doped congruent LiNbO 3 (LN) were successfully grown by the Czochralski method. The axial and radial gradient of the radio frequency furnace was controlled in order to obtain crack-free single crystals. Wafers were cut from the grown Ru-doped single crystal at different axial positions along the growth direction and subjected to various characterization analyses. Good optical homogeneity and low residual strain in the grown crystal is confirmed by the conoscopy patterns. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…More details of the crystal growth have been reported previously in ref. 39. In our earlier study of HRXRD on these Mg:LN single crystal sample it has been reported that the FWHM of the diffraction peak is ~ 29-112 arc sec signifying the good crystalline quality of the grown crystal [39].…”
Section: Crystal Growthmentioning
confidence: 83%
See 1 more Smart Citation
“…More details of the crystal growth have been reported previously in ref. 39. In our earlier study of HRXRD on these Mg:LN single crystal sample it has been reported that the FWHM of the diffraction peak is ~ 29-112 arc sec signifying the good crystalline quality of the grown crystal [39].…”
Section: Crystal Growthmentioning
confidence: 83%
“…LN is ferroelectric at room temperature with the R3c space group. Single crystals of LN can be grown from stoichiometric composition (SLN), with the Li/Nb molar ratio of 50:50 as well as from the congruent composition (CLN) with the Li/Nb ratio of 48.6:51.4 [7,8]. It has been well established that many of the physical properties of LN crystals depend on the composition.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the closeness of Ru with Fe, it is assumed that the doping effect of Ru in nonlinear crystals would be similar. The Ru-ion doping in NLO crystals has been studied, such as in Ru:LiNbO 3 , 28 Ru:Bi 12 SiO 20 , 27 Ru:Bi 4 Ge 3 O 12 , 29 Ru:Sr 0.61 Ba 0.39 Nb 2 O 6 , 30 and Ru:Bi 12 TiO 20 . 31 Like Fe, Ru-ion doping in LN may be supportive to improve the photorefractive characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%